Projecting regional climate and cropland changes using a linked biogeophysical-socioeconomic modeling framework: 2. Transient dynamics - Ahmed, Kazi Farzan; Wang, Guiling; You, Liangzhi; Anyah, Richard; Zhang, Chuanrong; Burnicki, Amy (American Geophysical Union, 2017)
Understanding climate-cropland interactions and their impact on future projections in West Africa motivated the recent development of a modeling framework that asynchronously couples four models for regional climate, crop growth, socioeconomics, and cropland allocation. This modeling framework can be applied to a future time slice using an equilibrium approach or to a continuous projection using a transient approach. This paper compares the differences between these two approaches, examines the transient dynamics of the system, and evaluates its impact on future projections. During the course of projection up to mid-century, food demand is projected to increase monotonically, while the projected crop yield shows a high degree of temporal dynamics due to strong climate variability. Such temporal dynamics are not accounted for by the equilibrium approach. As a result, the transient approach projects a generally faster future expansion of cropland, with the largest differences over Benin, Burkina Faso, Ghana, Senegal, and Togo. Despite the relative large differences between the two approaches in projecting land cover changes associated with cropland expansion, the projected future climate changes are fairly similar. While the additional cropland expansion in the transient approach favors a wet signal, both the transient and equilibrium approaches project a future decrease of rainfall in the western part of West Africa and an increase in the eastern part. For quantifying climate changes, the equilibrium application of the modeling framework is likely to be sufficient; for assessing climate impact on agricultural sectors and devising mitigation and adaptation strategies, transient dynamics is important.